1982
DOI: 10.1161/01.str.13.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nerves protect against blood-brain barrier disruption in the spontaneously hypertensive rat.

Abstract: bed. 4 Thus, we hypothesized that a reduction in SHR intraparenchymal cerebral vessel wall thickness after chronic denervation could lead to a significantly enhanced wall tension (tension = pressure X radius/wall thickness) 6 as blood pressure and vessel radius are increased. During basal conditions, a reduced wall thickness due to chronic sympathetic denervation would be expected to have little effect since cerebral vascular resistance is not altered over a wide range of arterial pressures or during hypocapni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In addition, attenuation of medial hypertrophy in spontaneously hypertensive and stroke-prone spontaneously hypertensive rats increased the susceptibility of the BBB to disruption during acute hypertension. 13,14 Therefore, it appears that hypertension-induced cerebral artery hypertrophy can stiffen the vascular wall, making cerebral arteries more resistant to forced dilatation during acute hypertension, thereby protecting the BBB. 5,6 Cerebral arteries can also undergo eutrophic remodeling in response to chronic hypertension, defined as a decrease in external and internal diameter such that cross-sectional area does not change.…”
mentioning
confidence: 99%
“…In addition, attenuation of medial hypertrophy in spontaneously hypertensive and stroke-prone spontaneously hypertensive rats increased the susceptibility of the BBB to disruption during acute hypertension. 13,14 Therefore, it appears that hypertension-induced cerebral artery hypertrophy can stiffen the vascular wall, making cerebral arteries more resistant to forced dilatation during acute hypertension, thereby protecting the BBB. 5,6 Cerebral arteries can also undergo eutrophic remodeling in response to chronic hypertension, defined as a decrease in external and internal diameter such that cross-sectional area does not change.…”
mentioning
confidence: 99%
“…10 It has been suggested that this long term effect is due to a "trophic" influence on smooth muscle proliferation in the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated sympathetic nerve activity to the cerebral vessels in SHR may be protective against stroke both acutely 8 -9 and chronically. 10 -" One can conjecture that alterations in superior cervical sympathetic nerve activity, possibly genetic in origin, may contribute to stroke in selected hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same experimental protocol that we used in our previous study. 1 Profound cerebral vasodilation was induced with acute hypertension (norepinephrine) and seizures (bicuculline). We hypothesized that if a reduction in SHR intraparenchymal cerebral vessel wall thickness was present after chronic denervation, it would lead to a significantly enhanced wall tension (tension = pressure X radius/wall thickness) 2 as blood pressure and vessel radius were increased.…”
mentioning
confidence: 99%
“…1 A possible "trophic" influence of sympathetic nerves on cerebral vessels of adult SHR with established hypertension has not been examined. Thus, the purpose of this study was to determine the effect of chronic sympathetic denervation on cerebral vessels of SHR when superior cervical ganglionectomy was performed in adulthood rather than adolescence.…”
mentioning
confidence: 99%